Neuropharmacology of Cevimeline and Muscarinic Drugs-Focus on Cognition and Neurodegeneration - Oleksak, Patrik; Novotny, Michal; Patocka, Jiri; Nepovimova, Eugenie; Hort, Jakub; Pavlik, Jan; Klimova, Blanka; Valis, Martin; Kuca, Kamil (International journal of molecular sciences, 2021)
At present, Alzheimer's disease (AD) and related dementias cannot be cured. Therefore, scientists all over the world are trying to find a new approach to prolong an active life of patients with initial dementia. Both pharmacological and non-pharmacological pathways are investigated to improve the key symptom of the disease, memory loss. In this respect, influencing the neuromodulator acetylcholine via muscarinic receptors, such as cevimeline, might be one of the therapeutic alternatives. The purpose of this study is to explore the potential of cevimeline on the cognitive functions of AD patients. The methodology is based on a systematic literature review of available studies found in Web of Science, PubMed, Springer, and Scopus on the research topic. The findings indicate that cevimeline has shown an improvement in experimentally induced cognitive deficits in animal models. Furthermore, it has demonstrated to positively influence tau pathology and reduce the levels of amyloid-β (Aβ) peptide in the cerebral spinal fluid of Alzheimer's patients. Although this drug has not been approved by the FDA for its use among AD patients and there is a lack of clinical studies confirming and extending this finding, cevimeline might represent a breakthrough in the treatment of AD.
Keywords: Neuropharmacology; Animals; chinuklidiny; Muscarinic Agonists; agonisté muskarinových receptorů; Neurodegenerative Diseases; kognitivní poruchy; thiofeny; neurodegeneration; cognition; cholinergic agonist; lidé; Pharmaceutical Preparations; neurodegenerativní nemoci; léčivé přípravky; cevimeline; Cognition Disorders; memory; evoxac; Thiophenes; SNI2011; AF102B; Quinuclidines; neurofarmakologie; zvířata; muscarinic receptors; Alzheimer disease; Humans